1999
DOI: 10.1159/000006912
|View full text |Cite
|
Sign up to set email alerts
|

Improved One-Year Survival afterAcute Myocardial Infarction in Iceland between 1986 and 1996

Abstract: During the last decade the treatment of patients with acute myocardial infarction (AMI) has changed dramatically. In order to evaluate the overall impact of these changes on mortality and morbidity, we collected data on all patients hospitalized for AMI in Reykjavik, Iceland, during the calendar years of 1986 and 1996. Demographical characteristics of AMI patients did not change significantly between study periods. One-year mortality decreased from 26.3 to 19.7% (p < 0.05). Patients discharged with aspirin or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In 4 of the 7 studies accepted to be of good quality, non-significant results regarding depression and post-MI mortality were reported [13, 17, 23, 31; ]Appendix 1], whereas in the three other studies a positive relation was reported [[5, 21, 26]; Appendix1]. In 10 of the 20 studies of medium quality, a positive relation was reported [1, 2, 8,14,15,16, 19, 20, 24, 25; ]Appendix 1], whereas in the remaining ten studies a non-significant relation was reported [3, 6, 10, 12, 18, 22,27,28,29,30]; Appendix 1].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In 4 of the 7 studies accepted to be of good quality, non-significant results regarding depression and post-MI mortality were reported [13, 17, 23, 31; ]Appendix 1], whereas in the three other studies a positive relation was reported [[5, 21, 26]; Appendix1]. In 10 of the 20 studies of medium quality, a positive relation was reported [1, 2, 8,14,15,16, 19, 20, 24, 25; ]Appendix 1], whereas in the remaining ten studies a non-significant relation was reported [3, 6, 10, 12, 18, 22,27,28,29,30]; Appendix 1].…”
Section: Resultsmentioning
confidence: 99%
“…In 4 of the 8 studies, where depression was assessed based on interviews, a positive relation between depression and post-MI mortality was found [5, 16, 21, 26; ]Appendix 1], whereas a non-significant relation was reported in the other four studies [[13, 22, 23, 31; ]Appendix 1]. In 5 of the 9 studies, where the BDI was applied, a positive relation was reported [1, 8, 14, 15, 26; ]Appendix 1], whereas a non-significant relation was reported in three studies [18, 27, 30; ]Appendix 1], and the sixth and last study [7]; Appendix 1] failed to report on this.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations